Economia colaborativa enquanto modelo da nova gestão pública - Silva, Moisés Mark Porcinio da (Universidade Federal Rural do Semi-Árido, 2018)
Public management have been facing contemporary challenges that leads to a search for innovative and permanent solutions in the provision of services to citizens. Can collaborative economics, driven by the phenomenon of globalization, make possible a new approach within the paradigm of new managerialism in the public sector? This issue becomes mora relevant as limitations are observed in the management of municipal public services. Moreover, society has increasingly been confronted with the neglect and misuse of public resources by managers. Thus, this dissertation had as its central objective to analyze if the collaborative management of the public service can improve the governance and the municipal institutional capacities. The methodological approach was qualitative exploratory descriptive. Interviews were conducted with current public managers from five municipalities in the northeastern semi-arid region and with the president of FEMURN, and the data collected were treated using the content analysis technique. The observed results confirm the managerial limitations in the management of the municipal services, as well as indicates that the collaborative management of the public service can bring a positive perspective from the effective and direct action of the citizen. However, the interest of public managers and the willingness to develop effective mechanisms to encourage collaboration is still rooted in public inheritance and creates obstacles to the collaborative management innovation of public services. The lack of interest of citizens in collaborating in the public sphere is cited as the main barrier to this the public collaborative management model
Keywords: Economia Colaborativa; Governança; Capacidades Institucionais; Cooperativismo; Serviços Públicos; Collaborative Economics; Governance; Institutional Capacities; Cooperativism; Public Services; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA